The Evolution of Transport Terminology - Turdalieva , Mokhlaroyim (The Lingua Spectrum, 2025)
The article is devoted to transport terminology evolution through Uzbek and English dialects during pre-globalization times up to modern technological era changes. This paper investigates the historical transformation of transport terminology between the Uzbek and English languages because it shows cultural developments alongside technological and historical modifications, and demonstrates their disparate responses to globalization. The research utilizes historical methodology to study the development patterns of transport terminology in Uzbek across the Turkic ancient period and Soviet era and in English from Old English to the twentieth century. Studies indicate that both languages extensively adapted words from other languages, yet English terms developed rapidly when the Industrial Revolution began and the Soviet period enabled dramatic growth in Uzbek words. Through the 21st century, the both Uzbek and English languages converged their terms between logistika for "logistics" and e-logistics while reflecting joint technological progress. Research findings create opportunities for language education practitioners, translation experts, and governmental authorities to develop uniform terminology as well as build cross-cultural communication in today’s global environment. Research adds valuable insights regarding the process of language adaptation to change while providing an analytical approach for continued work on terminology development.